The Origin of Daniel’s Four Empires Scheme Re-Examined - Lucas, Ernest (Tyndale bulletin, 1989)
An exploration of possible literary precursors for the Four Empires scheme found in Daniel 2 and 7, proposing that there is no compelling evidence of Persian influence.